3D Printing of Living Responsive Materials and Devices. Issue 4 (5th December 2017) - Liu, Xinyue; Yuk, Hyunwoo; Lin, Shaoting; Parada, German Alberto; Tang, Tzu‐Chieh; Tham, Eléonore; de la Fuente‐Nunez, Cesar; Lu, Timothy K.; Zhao, Xuanhe
Abstract: 3D printing has been intensively explored to fabricate customized structures of responsive materials including hydrogels, liquid‐crystal elastomers, shape‐memory polymers, and aqueous droplets. Herein, a new method and material system capable of 3D‐printing hydrogel inks with programed bacterial cells as responsive components into large‐scale (3 cm), high‐resolution (30 μm) living materials, where the cells can communicate and process signals in a programmable manner, are reported. The design of 3D‐printed living materials is guided by quantitative models that account for the responses of programed cells in printed microstructures of hydrogels. Novel living devices are further demonstrated, enabled by 3D printing of programed cells, including logic gates, spatiotemporally responsive patterning, and wearable devices. Abstract : A new paradigm in 3D printing is reported by using genetically programed cells as active components to print living materials and devices. The design principle and general method are provided to fabricate large‐scale, high‐resolution living materials, which are capable of integrating engineered cells into hydrogel constructs that maintain high viability of cells and respond to signaling chemicals in programed manners.